Sound as Environment in Tom Konyves’ Urban Pastorals - Bénédicte CHORIER-FRYD (E-REA)
The poetry of Canadian poet Tom Konyves offers sketches of urban pastoral in which sounds play a central part. They are constitutive of the environments construed by the poems as well as of the poems as environmental forms. Resting on Susanna Lidström and Greg Garrard’s conception of “environmental thinking” in the poetic process, this paper looks at two poems (a long textual piece and a “videopoem” – a hybrid poetic form bringing together text, image and sound to produce a poetic experience), and examines the ways in which sounds contribute to create the complex environment of the poem, poised between presence and dissolution.